Land Suitability Analysis For Brackishwater Aquaculture Development In In Morotai Island District - Rusdi; Wahidin, Nurhalis; Muhammad Aris; Taufiq Abdulah (Jurnal Ilmiah Platax, 2024)
This study aims to analyze the land suitability in the coastal area of Pulau Morotai Regency for whiteleg shrimp. The research was conducted in Raja Village. The observed parameters include infrastructure data such as distance to the market, distance to the highway, and distance to the hatchery. Water quality parameters are water temperature, salinity, dissolved oxygen (DO), water pH, total ammonia nitrogen (TAN), nitrite, nitrate, phosphate, and plankton abundance. Meanwhile, the observed soil quality parameter is soil pH. Land suitability analysis was conducted using geographic information systems and drones. The results show that the distances to the market, highway, and hatchery are >12 km, >5 km, and >12 km, respectively. Water temperature ranges from 15.40-27.10 ℃, salinity is 0 ppt, DO ranges from 1.00-2.20 mg L-1, water pH ranges from 6.00-7.00, TAN ranges from 0.001-0.043 mg L-1, nitrite ranges from 0.017-0.070 mg L-1, nitrate ranges from 0.005-0.045 mg L-1, phosphate ranges from 0.006-0.048 mg L-1, and plankton abundance is 2.3×109 cells L-1. Meanwhile, soil pH ranges from 4.00-7.00. The analysis indicates that the coastal area of Raja has 1000 Ha of marginally suitable land (S3) and 1000 Ha of unsuitable land (N) for brackishwater aquaculture development. Keywords: Brackishwater aquaculture; Coastal area; Pulau Morotai Regency; Whiteleg shrimp. Abstrak Penelitian ini bertujuan menganalisis kesesuaian lahan di pesisir Kabupaten Pulau Morotai untuk budidaya udang vaname. Penelitian dilakukan di Desa Raja, Kabupaten Pulau Morotai. Parameter yang diamati meliputi data infrastruktur yang diamati adalah jarak ke pasar, jarak ke jalan raya dan jarak ke hatchery. Data parameter kualitas air yang diamati adalah suhu perairan, salinitas, oksigen terlarut (DO), pH air, total ammonia nitrogen (TAN), nitrit, nitrat, fosfat dan kelimpahan plankton. Sementara data parameter kualitas tanah yang diamati adalah pH tanah. Analisis kesesuaian lahan dilakukan menggunakan sistem informasi geografis (GIS) dan drone. Hasil penelitian menunjukkan bahwa jarak ke pasar, jalan raya, dan hatchery masing-masing >12 km, >5 km, dan >12 km. Suhu air 15,40 – 27,10 ℃, salinitas 0 ppt, DO 1,00 – 2,20 mg L-1, pH air 6,00 – 7,00, TAN 0,001 – 0,043 mg L-1, nitrit 0,017 – 0,070 mg L-1, nitrat 0,005 – 0,045 mg L-1, fosfat 0,006 – 0,048 mg L-1, dan kelimpahan plankton 2,3 × 109 Sel L-1. Sementara pH tanah 4,00 – 7,00. Analisis menunjukkan kawasan pesisir Raja memiliki 1000 Ha lahan yang cukup sesuai (S3) dan 1000 Ha yang tidak sesuai (N) untuk pengembangan budidaya air payau. Kata kunci: Budidaya air payau; Kabupaten Pulau Morotai; Kawasan pesisir; Udang vaname.